Damaging novel mutations in PIGN cause developmental epileptic-dyskinetic encephalopathy: a case report - Maoqiang Tian; Jing Chen; Juan Li; Hong Pan; Wenting Lei; Xiaomei Shu (BMC, 2022)
Abstract Background Mutations in PIGN, resulting in a glycosylphosphatidylinositol (GPI) anchor deficiency, typically leads to multiple congenital anomalies-hypotonia-seizures syndrome. However, the link between PIGN and epilepsy or paroxysmal non-kinesigenic dyskinesia (PNKD) is not well-described. This study reported a patient with PIGN mutation leading to developmental and epileptic encephalopathy and PNKD, to expand upon the genotype-phenotype correlation of PIGN. Case presentation During the first 10 days of life, a girl exhibited paroxysmal staring episodes with durations that ranged from several minutes to hours. These episodes occurred 2-5 times daily and always occurred during wakefulness. Ictal electroencephalography revealed no abnormalities, and PNKD was diagnosed. The patient also exhibited severely delayed psychomotor development and generalized seizures at the age of 4 months. Results of brain magnetic resonance imaging and metabolic screenings were normal, but trio-based whole-exome sequencing identified two novel compound heterozygous PIGN mutations (NM_176787; c.163C > T [p.R55 > X] and c.283C > T [p.R95W]). Flow cytometry analysis of the patient's granulocytes revealed dramatically reduced expression of GPI-anchored proteins. This indicated that the mutations compromised GPI functions. The patient got seizure-free for 1 year, and her dyskinesia episodes reduced significantly (1-2 times/month) after treatment with levetiracetam (600 mg/day) and clonazepam (1.5 mg/day). No progress was observed with respect to psychomotor development; however, no craniofacial dysmorphic features, cleft lip/palate, brachytelephalangy with nail hypoplasia, and internal malformations have been observed until now (6 years of age). Conclusion This is the first study to document developmental and epileptic encephalopathy with PNKD in a human with PIGN mutations. This report expanded our understanding of the genotype-phenotype correlation of PIGN, and PIGN may be considered a potentially relevant gene when investigating cases of epilepsy or PNKD.